1999
DOI: 10.1152/ajpregu.1999.277.3.r812
|View full text |Cite
|
Sign up to set email alerts
|

Organization of rat circadian rhythms during daily infusion of melatonin or S20098, a melatonin agonist

Abstract: Daily administration of melatonin or S20098, a melatonin agonist, is known to entrain the free-running circadian rhythms of rats. The effects of the duration of administration on entrainment were studied. The animals demonstrated free-running circadian rhythms (running-wheel activity, body temperature, general activity) in constant darkness. Daily infusions of melatonin or S20098 for 1, 8, or 16 h entrained the circadian rhythms to 24 h. Two daily infusions of 1 h (separated by 8 h) entrained the activity peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 60 publications
5
58
0
6
Order By: Relevance
“…Similarly, previous studies have shown that diurnal MEL ingestion affect essentially cognitive performances more than physical ones (6). For this reason, it should be noted that timing of MEL administration could influence specially the circadian rhythm of physiological parameters (17). In this way, morning MEL administration has been shown to phase delay circadian rhythms, while its administration in the late afternoon advanced it (19).…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, previous studies have shown that diurnal MEL ingestion affect essentially cognitive performances more than physical ones (6). For this reason, it should be noted that timing of MEL administration could influence specially the circadian rhythm of physiological parameters (17). In this way, morning MEL administration has been shown to phase delay circadian rhythms, while its administration in the late afternoon advanced it (19).…”
Section: Discussionmentioning
confidence: 67%
“…The distal end of the catheter was placed on a swivel fixed to a bar hung from the top of the cage. This method has been previously described, except that the catheter was implanted subcutaneously (Pitrosky et al, 1999). The swivel was connected to a syringe carried by a pump (Harvard Apparatus, Holliston, MA, USA) controlled by an electronic timer.…”
Section: Methodsmentioning
confidence: 99%
“…Nonphotic cues (eg transient behavioral arousal associated with motor activity) studied in nocturnal mammals are capable of inducing phase-advances especially when applied during the middle of the day (ie the resting period in nocturnal species), with little or no resetting effects during the night (for review, see Challet and Pevet, 2003). Propofol anesthesia produces phase advances in the late subjective day, similar to treatment with exogenous melatonin (Pitrosky et al, 1999). As far as we are currently aware, besides general anesthesia the only other synchronizing cues which share the ability to produce circadian phase-advances in the early subjective night are dark pulses applied in constant light (Dwyer and Rosenwasser, 2000;Mendoza et al, 2004).…”
Section: Chronobiotic Effects Of Propofol Anesthesiamentioning
confidence: 99%
“…In rats and hamsters with free-running circadian rhythms, pharmacological doses of exogenous MEL are capable of synchronizing the circadian rhythms of locomotor activity and MEL synthesis (see Redman et al, 1983;Armstrong and Chessworth, 1987;Humlova and Illnerova, 1990;Kirsch et al, 1993;Drijfhout et al, 1996b;Grosse and Davis, 1998;Pitrosky et al, 1999;FIG. 2. Schematic representation of the different theoretical models explaining how the photoperiodic MEL endocrine message is decoded.…”
Section: B Regulation Of Circadian Rhythmsmentioning
confidence: 99%